Children’s Agency in Jory John’s The Good Egg - Shirleen Felicia Limantara; Liliek Soelistyo (Kata Kita: Journal of Language, Literature, and Teaching, 2025)
In recent decades, American children's literature has increasingly highlighted children’s agency, reflecting broader cultural shifts toward recognizing children's autonomy and decision-making abilities. This paper analyzes the exercises of agency and the triggers behind them in a picture book titled The Good Egg by Jory John. Drawing on Bandura’s Agency Theory, we analyze the exercises of agency done by the main character and the triggers that caused them to exercise it. The analysis reveals that the Good Egg exercises his agency by making proactive commitments, future planning, self-regulation and motivation, and self-reflection. While his agency initially appears rigid, often rooted in idealized or externally influenced standards, it gradually evolves into a more reflective form. In addition, he exercises his agency after being triggered by his past experiences. Ultimately, the main character’s exercise of agency, including the triggers behind them, illustrates ways for young readers to use agency in their daily lives.